Descemet’s membrane detachment: An updated comprehensive review of etiopathogenesis, diagnosis, and management - Abhijeet Beniwal; Murugesan Vanathi; Anitha Venugopal; Sunita Chaurasia; Radhika Tandon (Indian Journal of Ophthalmology, 2024)
The Descemet membrane (DM) is the basement membrane of corneal endothelial cells, which are responsible for maintaining corneal transparency. DM detachment (DMD) can occur due to various reasons, with the most common etiology being post-surgical. Older age, blunt instruments, and faulty surgical technique predispose to the intraoperative or postoperative occurrence of DMD, and one should have a high index of suspicion for DMD in cases with unexplained or an atypical pattern of corneal edema after surgery. Prompt intervention for DMD management is imperative to effect early visual rehabilitation, decrease corneal morbidity, and avoid permanent damage leading to scarring of the cornea. Various classifications of DMD and management protocols have been described. Anterior-segment optical coherence tomography (AS-OCT) imaging is the most effective imaging to detect DMD and quantify its extent. Desmetopexy with air/gas is the initial treatment of choice and could be aided by suture fixation. Non-responsive cases might need endothelial keratoplasty.